Aspects of Responsible Tourism - A Quantitative Approach - Olimpia State; Daniel Bulin (Amfiteatru Economic Journal, 2016)
The concept of responsibility is well-known, but its association with tourism and connections with different aspects studied extensively, such as ethics, social responsibility, sustainable development and sustainable tourism, offers multiple research options. The main aim of this article is to define responsible tourism and to characterize responsible tourist. To define responsible tourism were seeking answers to the following questions: What are the main characteristics of responsible tourism? What known concepts can be associated with responsible tourism and with which forms of tourism is more suitable? And who are stakeholders in promotion and development of res ponsible tourism principles? To characterize responsible tourist, research answer to the following questions: What aspects define a responsible tourist? And, in this context, is a responsible attitude to travel and discover your own country? A secondary objective of the research is the statistical testing of correlations between respondents' characteristics and their opinion about the responsibility in tourism. The study is based on quantitative research - a questionnaire applied to Romanian tourists in the period of March-May 2015.
Keywords: L83; C10; 330; Responsible tourism; responsible tourist; quantitative research; survey; Pearson correlation